Salud mental de los periodistas que cubren temas de orden público en Colombia (2025)
Colombia is a country historically marked by conflict and violence. Journalists play a crucial role in staying informed and reporting on every event presented, whether through investigation or live coverage. This study aims to analyze the impact that journalists have on their mental health when carrying out their work covering conflict, public order, judicial and related issues. To do this, a bibliographic review of academic articles was carried out and interviews were carried out with 12 journalists to obtain a comprehensive view of the topic. The results indicate that emotional burden, psychological support and even economic conditions are determining factors in the mental health of journalists. This study highlights and makes evident the need to review the conditions of journalists in order to find a solution that can reduce the impact that the profession has on their mental health, and also emphasizes the need to continue studies on this topic to achieve a deep understanding of the needs that these journalists have in Colombian territory.